Osseointegrative effect of rhBMP-2 covalently bound on a titan-plasma-spray-surface after modification with chromosulfuric acid in a large animal bone gap-healing model with the Göttingen minipig - Lingner, Manuel; Lehmann, Lars; Mauermann, Eckhard; Obertacke, Udo; Schwarz, Markus (Journal of orthopaedic surgery and research, 2018)
Bone morphogenetic proteins play an important role as osseointegrative factors. It is used widely in orthopedic research and surgery to enhance the osseointegrative potential of implants, e.g., in spinal fusion or alveolar socket augmentation. The aim of the present study was to investigate the benefit of rhBMP-2 on a titan plasma spray (TPS) layer after a special modification with chromosulfuric acid (CSA) at different postoperative times, regarding osseoconduction and osseoinduction.